The rise of distributed energy resources: a case study of India’s power market - Poudineh, R; Mukherjee, M; Mukherjee, M; Elizondo, G (Oxford Institute for Energy Studies, 2021)
As the world’s third-biggest emitter of greenhouse gases, India has pledged to achieve net-zero carbon emissions by 2070. The electricity sector is at the forefront of decarbonisation initiatives and distributed energy resources (DERs) are expected to play a key role in enabling the country to eventually transition away from fossil fuel power generation (especially coal). DERs are physical or virtual assets that are located close to demand across the distribution grid, and can provide value to the power system, individual customers, or both. As the share of traditional flexible fossil fuel generation declines in the power mix, distributed generation, energy storage, and demand response will become important sources of system flexibility. Specifically, the rise of EVs (electric vehicles) and of electricity demand for cooling services provide significant opportunities for decentralized flexibility. However, the Indian power sector requires a range of reforms to bring it into line with the rise of the decentralization paradigm. These include in the areas of market architecture, coordination between transmission and distribution network operators, reforming the distribution sector and rationalisation of retail tariffs. In terms of market architecture, the country needs to move towards a two-sided market in which both supply-side and demand-side resources can participate. This requires removing barriers to the entry of aggregators, investment in ICT infrastructure and distribution grid modernization, and the establishment of liquid short-term electricity markets, local flexibility markets, and ancillary service markets. Also, a more effective coordination mechanism between transmission and distribution network operators is needed to improve visibility and control over DERs and enable a better utilization of these resources for both local grid congestion management as well as national grid balancing. The more complex issues, however, lie in the distribution sector. The current scope of distribution licensees’ operation includes both network and retailing, which means that the state distribution companies (Discoms) will not benefit from customer-owned DERs; they thus have an incentive to resist their uptake. The State Discoms are also in poor financial health due to a range of factors such as poor management, non-cost reflective retail tariffs, and a high level of AT&C (aggregated technical and commercial) energy losses. This prevents them from investing in grid modernization and digitalization. Finally, retail tariffs in India are lower than the actual costs of supply for residential consumers; this makes investment in DERs uneconomic for this class of customers, whereas a higher rate incentivizes grid defection among C&I (commercial and industrial) customers, with consequences for the revenues of distribution utilities.